The Development of E-Comics in Integrated Science and Religious Values for 5th Grade Students - Zeva Adi Fianto; Fitri Indriani; L.Y. Aminas (The Indonesian Institute of Science and Technology Research, 2023)
The context for this research project is the insufficient availability of innovative learning materials and the divide between general science and religious knowledge in education. In primary schools, science subjects are taught with a minimal use of technology for teaching materials. This study aimed to outline the steps taken, quality, and feasibility of e-comics in teaching integrated science and religious values to 5th-grade primary school students. The research process followed the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. Both qualitative and quantitative data were gathered to support the research. Qualitative data were collected through expert validation, teacher assessments, and feedback from the students who were the subjects of the study. The average score from expert validation, teacher assessments, and student feedback was 3.80. Based on this score, it can be concluded that the e-comic media is suitable for integrated science and religious education for 5th-grade primary school students and falls under the